2016
DOI: 10.1055/s-0042-104199
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Exploration of Concussion and Strength Performance in Youth Ice Hockey Players

Abstract: The objective of this study was to describe the effect of concussion on upper and lower body strength in children and youth athletes. The participant group was made up of 178 unique male and female ice hockey players (ages 8-14 years). Using a 3-year prospective longitudinal research design, baseline and post-concussion data on hand grip strength, jump tests, and leg maximal voluntary contraction were collected. Using a linear mixed-effects model, no significant differences were found when comparing the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…32 For example, decreased maximum strength has been reported after concussion. 38 Concussion can also affect the cervical spine proprioception, vestibular-ocular system, and visual systems that result in decreased postural stability. 5 Poor postural stability has been associated with ankle sprain, one of the most common lower extremity MSK injuries in sports.…”
Section: Physiological Reasoning Behind Increased Injury Rate After Cmentioning
confidence: 99%
“…32 For example, decreased maximum strength has been reported after concussion. 38 Concussion can also affect the cervical spine proprioception, vestibular-ocular system, and visual systems that result in decreased postural stability. 5 Poor postural stability has been associated with ankle sprain, one of the most common lower extremity MSK injuries in sports.…”
Section: Physiological Reasoning Behind Increased Injury Rate After Cmentioning
confidence: 99%
“…Baseline levels of somatization are strongly predictive of postinjury symptom reports (Nelson et al, 2016), and athletes with concussion may not cope as well after injury compared to those with other types of injuries (Kontos et al, 2013). Increased symptoms of depression have been found in high school and collegiate athletes with concussion up to 14 days postinjury with associated neurocognitive decrements (Kontos, Covassin, Elbin, & Parker, 2012), and postinjury changes in mood and activity level can serve to maintain symptoms (Reed, Taha, Monette, & Keightley, 2016). In a comprehensive review of the literature on psychological factors and persistent postconcussion symptoms, Broshek, De Marco, and Freeman (2015) reported that the neurobiological effects of concussion can cause anxiety and depression symptoms, and that psychosocial factors such as preinjury anxiety or misattribution of symptoms may contribute to prolonged recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Study results adds to emerging literature on motor control impairments after SRC, and specifically adds to research pertaining to strength after SRC. 14,34 Neurophysiological changes, such as increased cortical inhibition and increased motor activation threshold, 26 make it plausible that force generation capacity could be suppressed after SRC. It is unknown if this magnitude of strength deficit would be sufficient to increase lower extremity musculoskeletal injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…21 Strength has not been examined extensively in the SRC population, and so far the results are inconclusive. 14,16,33,34,36 Some studies have reported reduced hand and neck strength after SRC, 34,36 while other studies have found no change in hand or neck strength. 16,33 A study of military personnel with or without a concussion in the past year found no difference in isokinetic quadriceps and hamstring strength.…”
mentioning
confidence: 99%